A Case Report on Spontaneous Coronary Artery Dissection Managed by Percutaeneous Coronary Intervention (PCI) - Karmoker, Kajal Kumar; Dutta, Bijoy; Rashid, Mohammad Bazlur; Alam, Mohammad Ashraful; Kawsar, ABM Riaz; Siddika, Khandaker Aisha; Rahman, Mohammad Walidur (Bangladesh Heart Journal, 2021)
Background: Spontaneous coronary artery dissection (SCAD) is frequently underdiagnosed and often considered as a rare cause of acute coronary syndrome (ACS). Although it predominantly affects young women in the peripartum period, it can also occur in men. Most of the reported dissections have occurred in the left anterior descending coronary artery. The optimal treatment modalities are yet to be defined. Case Summary: A 50- year-old man who presented to us at National Institute of Cardio-Vascular Diseases (NICVD), Dhaka with an acute Non-ST-elevation myocardial infarction secondary to a spontaneous dissection of the Left anterior descending coronary artery. Due to ongoing chest pain, percutaneous coronary intervention (PCI) was done with drug eluting stent (DES) successfully, and the patient was discharged from the hospital on medical therapy. Conclusion: All clinicians should remain vigilant and aware of this condition, as patient outcomes and treatment guidelines differ substantially from conventional atherosclerotic ACS. Although initial conservative strategy is preferred strategy in SCAD management but timely intervention is warranted in selected cases. Bangladesh Heart Journal 2021; 36(2): 151-157